Pengaruh Model Pembelajaran Think Pair Share Berbantuan Powerpoint Interaktif Terhadap Pemahaman Konsep Materi Interaksi Antara Komponen Penyusun Ekosistem - Apria Rizki Pratiwi; Zenia Lutfi Kurniawati; Ruqoyyah Nasution; Nelda Anasthasia Serena; Suparno Putera Makkadafi (PendIPA Journal of Science Education, 2026)
This study aimed to determine the effect of the Think Pair Share (TPS) learning model assisted by interactive PowerPoint on students’ conceptual understanding of interactions among ecosystem components in Grade VII of SMP Negeri 7 Samarinda. This research employed a quasi-experimental method with a Non-Equivalent Control Group Design. The sample consisted of Class VII A as the experimental group and Class VII B as the control group, each consisting of 24 students. The sampling technique used was purposive sampling. Data were analyzed using normality tests, homogeneity tests, the Independent Sample t-test, and N-Gain analysis. The results showed that the average post-test score of the experimental class was 81, which was higher than that of the control class 66. The N-Gain analysis revealed an average score of 0.49 in the experimental class and 0.29 in the control class. Furthermore, the Independent Sample t-test showed a significance value of 0.000 < 0.05. Based on these findings, it can be concluded that the Think Pair Share (TPS) learning model assisted by interactive PowerPoint has a significant effect on students’ conceptual understanding in Grade VII of SMPN 7 Samarinda.